A Statistical Study of Technological Trends in Logistics: Patent Analysis - Chala Tеtyana G.; Hrynchak Nataliia A. (Problemi Ekonomiki, 2019)
The aim of the study is to develop a methodology for constructing series for distribution of patents based on selected characteristics, to analyze patterns in the structure of logistics processes and structural changes in them as an information base for a statistical study of technological trends in logistics. It is determined that research on technological trends is becoming very relevant for developing a successful technological strategy in logistics, taking into account the strategic importance of identifying opportunities for and threats to technological development while achieving sustainable competitiveness in the logistic market. Given the rapid pace of development of technology, both in logistics and related fields, logistics service providers need methodological support and relevant patent data to facilitate research on technological trends to increase their competitiveness. It is determined that using the method of expert assessments, qualification and company analysis in studying technological trends in logistics under modern conditions is ineffective, while statistical study of technological trends based on patent analysis in logistics is underestimated. The necessity of a statistical study of technological trends in logistics using a 4-stage methodology for conducting patent analysis is substantiated. The proposed methodology involves the use of the Latent Dirichlet Allocation (LDA), which allows determining the logistics related technological topics behind patents. In addition, information on technological topics and their trends, obtained as a result of the proposed methodology for patent analysis, will help to better understand the technological landscape in logistics.